A longitudinal study of the protective influence of youth assets on juvenile arrest. (28th October 2019) - Lensch, Taylor; Clements-Nolle, Kristen; Oman, Roy F; Lu, Minggen
Abstract: Background: The objective of this study was to determine the separate and cumulative influence of individual, family and community assets on juvenile arrest rates in a cohort of youth. Methods: Five waves of data were collected from 1111 youth and their parents living in randomly sampled census tracts in a Midwestern state. Computer-assisted, in-person data collection methods were used to measure assets within individual (six assets), family (four assets) and community (six assets) domains. Extended Cox models were used to assess the relationship between the number of assets and time to first juvenile arrest, while controlling for known confounders. Results: Nine of 16 assets across individual, family and community domains were prospectively associated with a reduction in arrest rates. There was a relationship between the number of assets youth possess within individual, family and community domains and rates of arrest. For example, compared to youth with zero to one community assets, those with three [adjusted hazard ratio (AHR): 0.52; 95% confidence interval (CI): 0.30–0.88], four [AHR: 0.57; 95% CI: 0.34–0.97] or five to six [AHR: 0.45; 95% CI: 0.25–0.82] community assets had lower risk of arrest. Conclusions: Public health efforts focused on developing policies and programs to promote asset building across multiple domains of influence are warranted.